Modelling hydrolytic, thermal, and mechanical degradation of PLA during single-screw extrusion (2024)
Since melt processing causes degradation of poly(lactic acid) or PLA, it is crucial to understand the effect of extrusion conditions on the molecular weight reduction. Kinetic models found in literature are promising tools to describe hydrolytic, thermal, and mechanical degradation during extrusion. In order to use these models, extrusion parameters (that are equipment dependent) should be translated into the four fundamental parameters that determine degradation: moisture content in PLA, residence time, shear stress history and temperature history. This work presents a methodology to use numerical simulations to translate extrusion parameters into fundamental parameters. The results show that numerical simulations can be used successfully to describe the extrusion process based on residence time, shear stress history, and temperature history.